Physical Fitness Levels and its Relationship with Self-concept Profile in Primary Schoolchildren aged 8-11 years of the Region of Murcia - ANDRÉS ROSA GUILLAMÓN (Federación Extremeña de Balonmano; University of Extremadura, 2016)
Introduction and objectives. Among the determinants of physical fitness, the aerobic capacity, the muscular strength and the weight status are important biological markers of health status in childhood. There are scientific evidence of the relationship between physical fitness and self-concept in young adults. However, few studies have analyzed these relationships prior to adolescence stages. The main aim of this Dissertation was to examine the level of fitness in primary schoolchildren and to analyze its possible relationship with the self-concept profile in the Region of Murcia. Methods. A total of 512 students (284 women) aged 8-11 years from the Region of Murcia participated in this cross-sectional and relational ex post facto study where physical fitness (Battery ALPHA-Fitness) was evaluated. Weight status (normal-weight, overweight and obesity) was categorized according to standard criteria. Self-concept was evaluated by the Self-Concept Scale for Children of Piers. Results. Data analysis showed that: a) physical fitness is positively associated with self-concept; b) aerobic capacity and muscular strength are positively associated with self-concept; c) weight status was inversely associated with the self-concept; d) weight status is inversely related to overall fitness; e) males have a higher physical self-concept; f) males have a better level of overall fitness. Conclusions. The results of this dissertation suggest that schoolchildren with a higher level of fitness (especially aerobic capacity and muscular strength) have a better global self-concept profile than their peers with a medium to low level. The schoolchildren with normal weight have a better overall self-concept than their peers with overweight and obesity. The schoolchildren with a BMI within healthy parameters show a better level of overall fitness (especially aerobic capacity). These findings highlight the need to promote the engagement and participation of students in physical and sports activities, which contribute to improving your overall physical fitness, given the positive relationship observed between the physical fitness and the different dimensions of self-concept as well as the global self-concept.